2021
DOI: 10.1177/11786302211060150
|View full text |Cite
|
Sign up to set email alerts
|

Household Water Treatment Practice and Associated Factors in Gibe District Southern Ethiopia: A Community Based Cross-Sectional Study

Abstract: Background: Household water treatment practice or managing water at the point-of-use provides a means of improving drinking water quality and preventing diarrheal diseases. However, evidence regarding household water treatment practice and associated factors in Ethiopia, particularly in Southern Ethiopia are limited. This study was, therefore, designed to assess household water treatment practice and associated factors among households in Southern Ethiopia. Methods: A community-based cross-sectional study desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
2
11
2
Order By: Relevance
“…When compared to the studies conducted in Ethiopia, the finding is slightly lower than the previous studies, particularly in Burie, Northwest Ethiopia (44.8%), Gibe (34.3%), and Bahir Dar, Northwest Ethiopia (34%). 21 , 32 , 33 Whereas the current finding was slightly greater than a study conducted in Dabat, Northwest Ethiopia, 23.1%; Degadamot, North West Ethiopia (14.2%); and Harar, Eastern Ethiopia (16.5%). 23 , 34 , 35 This slight difference might be due to a difference in the time period and sample size and a variation in the level of community awareness of household-level water treatment.…”
Section: Discussioncontrasting
confidence: 73%
“…When compared to the studies conducted in Ethiopia, the finding is slightly lower than the previous studies, particularly in Burie, Northwest Ethiopia (44.8%), Gibe (34.3%), and Bahir Dar, Northwest Ethiopia (34%). 21 , 32 , 33 Whereas the current finding was slightly greater than a study conducted in Dabat, Northwest Ethiopia, 23.1%; Degadamot, North West Ethiopia (14.2%); and Harar, Eastern Ethiopia (16.5%). 23 , 34 , 35 This slight difference might be due to a difference in the time period and sample size and a variation in the level of community awareness of household-level water treatment.…”
Section: Discussioncontrasting
confidence: 73%
“…Households who fetched water twice per day were 2.8 times more likely to practice HWT than households who fetched water more than twice per day. This is in agreement with a study from north-west Ethiopia 5 , 26 and Nigeria. 36 The possible explanation might be due to the fact that those who were fetching water more frequently might have higher tendency to store their water, which in turn empowers them to treat their water, by storing.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with the study done Northwest Ethiopia (44.8%), 5 Nigeria (45%) 36 whereas it was lower than studies revealed from Zambia (72.6%), Peru 70.9%, 37 and a study in Western Pacific region (66.8%). 27 But it was higher than the findings from Ethiopian demographic health survey 2016 which is 7%, 34 Southern Ethiopia Gibe district revealed 34.3%, 26 northern Ethiopia Degadamot district 14%, 38 and in developing countries 33.3%. 39 It was also higher than studies revealed from outside Ethiopia such as in Biye community, Kaduna State of Nigeria 32.4%, in Eastern Mediterranean region 13.6%, 27 and in African region 18.2%.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations